Determination of antioxidant and phytochemical properties of premix extract of brown macroalgae Padinaaustralis, Sargassum licifolium and Stoechospermum marginatum from Chabahar coast, Southeastern Iran - Paria Akbary (تغذیه آبزیان)
Introduction: Macroalgae is one of the most important sources of cheap alternative feed for aquatic animals, which is also rich in nutritional and medicinal properties. Most importantly, they contain a wide range of bioactive agents such as phenols, sterols and flavonoids, many of which are not commonly found in land plants. These bioactives, including phenols and macroalgae extracts containing these compounds, have been investigated as feed additives in aquatic nutrition. Like other organisms, polyphenols have beneficial properties such as antimicrobial and antioxidant properties that improve growth performance, nutrient utilization, immunity, and disease resistance. The aim of this study was to investigate the phytochemical compounds (sterol, phenol and flavonoids) and grinding each of the macroalgae by an electric mill (Moulinex model), antioxidant activity (diphenylpicryl hydrazyl (DPPH)) of premix extracts of brown macroalgae Padina australis, Sargassum ilicifolium and Stoechospermum marginatum.Materials and methods: Brown macroalgae Sargassum ilicifolium, Nizimuddinia zanardini, Cystoseria indica, Padina australis and Stoechospermum marginatum were collected from Chabahar shores during low tide in December 2022 and after being transported to the laboratory, they were rinsed with freshwater to remove debris. Then they were dried in the shade and at the room temperature (25 °C). After grinding in a mixer, and turning into powder the algae were combined in a ratio of 1:1:1. Sterol was measured by gas chromatography, while phenol, flavonoids and antioxidant activity were measured by spectrophotometer. Statistical data analyses were performed using SPSS software and based on One-Way ANOVA test. The normality of the data was checked using the Kolmogorov-Smirnov test and the equality of variances was checked using the Levene test. After determining the significance of the difference between the means, Duncan's multi-range test was used to rank them at the probability level of p<0.05.Results: The results showed that sterol was the predominant sitostanol. The amount of total sterol, cholesterol and delta 5 avenasterol were 368.78 ± 24.12, 10.02 ± 2.12 and 3.54 ± 0.06 mg/100 g of dry matter, respectively. The highest phenolic content (132.46 ± 11.07 mg GAE/g extract), flavonoids (25.51 ± 0.67 mg QE/g extract) and anti-radical activity of DPPH (1967.32 ± 31.07μmol TE/g extract) were observed in ethanolic extract of premix macroalgae. The levels of phenol, flavonoids and antioxidant activity were higher in ethanol, ethanol-aqueous and aqueous extracts, respectively, and showed a significant difference (p<0.05).Conclusion: Overall, sitostanol was the predominant sterol of the macroalgae premix tested, and the ethanolic extract of the macroalgae premix showed the best flavonoid content, phenol, and antioxidant activity that can be recommended as a rich source of sterols and natural antioxidants for the food industry.